2017
DOI: 10.1536/ihj.16-278
|View full text |Cite
|
Sign up to set email alerts
|

Low Serum Levels of Eicosapentaenoic Acid and Docosahexaenoic Acid are Risk Factors for Cardiogenic Syncope in Patients with Brugada Syndrome

Abstract: SummaryThe n-3 polyunsaturated fatty acids (PUFAs), including eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), have antiarrhythmic effects, possibly via modulation of the cardiac ion channels. Nevertheless, it is unknown whether low serum levels of n-3 PUFAs are risk factors for ventricular fibrillation in patients with Brugada syndrome (BrS). We retrospectively reviewed data from 62 men with BrS and evaluated their serum levels of EPA and DHA, and the risk factors for sudden cardiac death, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…We reported that low serum EPA and DHA levels are risk factors for cardiogenic syncope in patients with Brugada syndrome 75 ) . Although the etiology of Brugada syndrome is multifactorial and involves genetic, environmental, and hormonal components, n-3 PUFAs can modulate cardiac ion channels, resulting in the prevention of ventricular arrhythmia.…”
Section: Other Preferable Effects Of N-3 Pufas For Preventing Cvdmentioning
confidence: 97%
“…We reported that low serum EPA and DHA levels are risk factors for cardiogenic syncope in patients with Brugada syndrome 75 ) . Although the etiology of Brugada syndrome is multifactorial and involves genetic, environmental, and hormonal components, n-3 PUFAs can modulate cardiac ion channels, resulting in the prevention of ventricular arrhythmia.…”
Section: Other Preferable Effects Of N-3 Pufas For Preventing Cvdmentioning
confidence: 97%
“…38) Previous reports have described the secondary prevention of sudden cardiac death and ventricular arrhythmias after myocardial infarction or heart failure via the use of omega-3 PUFAs. 39) The cardioprotective effects of ω-3 PUFAs are thought to be due to synergism among multiple mechanisms. 36) The results of previous studies and those of the present study suggest that the improvement of coronary microcirculation by EPA may protect against microvascular ischemia or reperfusion injury when AMI occurs in patients with stable AP.…”
Section: Discussionmentioning
confidence: 99%
“…For example, acute application of polyunsaturated fatty acids, in particular those of the n-3 class (PUFAs), inhibits I Na ( 97 ) and therefore may facilitate BrS. Yagi et al ( 98 ), however, suggested that n-3 PUFAs may prevent ventricular fibrillation in BrS, likely due to additional blockade of various other cardiac ion channels ( 68 ), including I to ( 99 ). High cholesterol and fat intake may constitute additional diet-related modulatory factors.…”
Section: Variable Expressivity In Scn5a Channelopamentioning
confidence: 99%